Antibacterial properties of selected freshwater microalgae against pathogenic bacteria - Das, B K; Jyothirmayee, Pradhan (Indian Journal of Fisheries, 2016)
Aqueous, ethanolic and methanolic extracts from four selected freshwater microalgae, Euglena viridis, Chlorella vulgaris,Microcystis aeruginosa and Spirulina platensis were examined for antibacterial activity by single disk diffusion method. Allfour algae revealed antibacterial properties. Best results were shown by the ethanolic extracts of E. viridis against Vibrioalginolyticus, Vibrio harveyi, Pseudomonas putida and Escherichia coli. Aqueous extracts of C. vulgaris also possessedantibacterial properties.